(0+50)x(1-60-60)x(0+10)=

Simple and best practice solution for (0+50)x(1-60-60)x(0+10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (0+50)x(1-60-60)x(0+10)= equation:


Simplifying
(0 + 50) * x(1 + -60 + -60) * x(0 + 10) = 0

Combine like terms: 0 + 50 = 50
(50) * x(1 + -60 + -60) * x(0 + 10) = 0

Combine like terms: 1 + -60 = -59
50x(-59 + -60) * x(0 + 10) = 0

Combine like terms: -59 + -60 = -119
50x(-119) * x(0 + 10) = 0

Combine like terms: 0 + 10 = 10
50x * -119x(10) = 0

Reorder the terms for easier multiplication:
50 * -119 * 10x * x = 0

Multiply 50 * -119
-5950 * 10x * x = 0

Multiply -5950 * 10
-59500x * x = 0

Multiply x * x
-59500x2 = 0

Solving
-59500x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-59500'.
x2 = 0.00

Simplifying
x2 = 0.00

Take the square root of each side:
x = {0.00}

See similar equations:

| 7y+6-12y= | | f(3)=6x+12 | | h(x)=0.10x+9.5 | | 6(u-8)-8u=28 | | 0x+0y=300 | | 2(-3x+5)=4[-4x+5(-x+3)] | | 9(z+3)-3(z-4)=3(z-2)+2(z-1) | | 6(4x-8)-8=6(x-3)+70 | | 2(x+1)-7=3x-15 | | 6x=3(x-2)+33 | | 2(x+2)=5(x-1)-6 | | 7(3n+4)=9(4n+7)+4 | | x+5+x=x+7+x+4+x+11 | | 18x-(8x-6)=46 | | 2x+44-3x=3-4x+5 | | 62(z-59)=z+81 | | -8(-8x-6)=16x-22 | | 2a-20.7=a+1.3 | | 21(4+3x)=336 | | 6x^2=6x-39 | | 6t-12t-2t= | | W+w+5w= | | 12+4(z-3)=-3z+5 | | -16x^2+96x-108=0 | | 21+4+3x=336 | | -16x+96x-108=0 | | 2x+5=-6x-11 | | 4x-28=3x+11 | | -5-(-7)-2-(-13)= | | y=1.2x+2.4 | | 6(x+8)=8+5x | | 128x-y=16 |

Equations solver categories